Narkotika Sebagai Bentuk Patologi Sosial: Analisis Normatif Terhadap Kebijakan Pemidanaan dan Rehabilitasi Dalam Hukum Nasional Indonesia - Radhwa Farah Azizah; Try Mustaqim; Nuraisyah Putri; Salsabila Ayu Pramita; Wevy Efticah Sary (GLOBAL SCIENTS PUBLISHER, 2025)
Drug abuse is a form of social pathology that has a multidimensional impact on public order, public health, and social stability. The main problem is evident in the continued dominance of a punitive approach in national policy, while the rehabilitation aspects required by law have not been implemented proportionally. This study analyzes the criminalization and rehabilitation provisions in Law No. 35 of 2009 on Narcotics and its derivative regulations using a normative juridical method with a legislative, conceptual, and doctrinal approach. The results show that national policy still tends to be repressive and not fully in line with the social pathology paradigm that emphasizes recovery. There is also a discrepancy between legal norms and practice, particularly regarding the placement of drug abusers as subjects of rehabilitation.